Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/ja103781u
|View full text |Cite
|
Sign up to set email alerts
|

Selective 2′-Hydroxyl Acylation Analyzed by Protection from Exoribonuclease

Abstract: Selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) is a powerful approach for characterizing RNA structure and dynamics at single-nucleotide resolution. However, SHAPE technology is limited, sometimes severely, because primer extension detection obscures structural information for ~15 nts at the 5′ end and 40–60 nts at the 3′ end of the RNA. Moreover, detection by primer extension is more complex than the actual structure-selective chemical interrogation step. Here we quantify covalent adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 30 publications
5
54
0
Order By: Relevance
“…Conversely, the intrinsic instability of the native helix P1 sequence contained within the TPP aptamer domain investigated here (4 bp) may also contribute allosterically to the dynamics of the P4/P5 junction. For many previous folding and structural investigations of the TPP aptamer domain, helix P1 was either extended or altered (15,22,(24)(25)(26)(27)(28) to promote aptamer stability and compaction. In this view, the inherent instability of helix P1 may contribute directly to the mechanism of TPP riboswitchmediated translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the intrinsic instability of the native helix P1 sequence contained within the TPP aptamer domain investigated here (4 bp) may also contribute allosterically to the dynamics of the P4/P5 junction. For many previous folding and structural investigations of the TPP aptamer domain, helix P1 was either extended or altered (15,22,(24)(25)(26)(27)(28) to promote aptamer stability and compaction. In this view, the inherent instability of helix P1 may contribute directly to the mechanism of TPP riboswitchmediated translation.…”
Section: Resultsmentioning
confidence: 99%
“…Such studies include 2-aminopurine fold analysis (22), small-angle X-ray scattering (SAXS) (23)(24)(25), RNase-detected selective 2′-hydroxyl acylation (26,27), isothermal titration calorimetry (28,29), as well as single-molecule optical-trapping methods in which force was applied via the 5′ and 3′ ends of the RNA to directly monitor the energy landscape of TPP riboswitch folding and unfolding (30). Investigations of this kind have provided an important framework for understanding global features of the TPP riboswitch aptamer domain, revealing that its structural compaction is enabled by physiological concentrations of Mg 2+ ions and enforced by TPP binding.…”
mentioning
confidence: 99%
“…However, the authors did not demonstrate that this preorganization included any tertiary structure. Most recently, Steen, et al chemically modified the thiM RNA in the absence of ligand and observed a pattern of protections indicative of fully formed secondary structure, but no tertiary structure (23). Our data are consistent with all the data (but not necessarily all the interpretations) in these prior studies, as well as with the SAXS studies mentioned above, and argue that any preorganization of the A. thaliana thiC aptamer involves the formation of helices P1-P5 and the juxtaposition of those helices due to stacking or primary connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…28,32 In another example, SHAPE analysis of the free and unbound thiamine pyrophosphate sensing (TPP) riboswitch aptamer emphazised that, in the ligand-free state, the aptamer consists of five well-formed and stable helices that are linked by highly dynamic singlestranded regions, suggestive of a structure with little or no stable tertiary interactions. 33 Noteworthily, hydroxyl radical footprinting and UV-cross-linking have also been alternatively applied to verify preorganized states of the glmS riboswitch in the absence of ligand. 34 While biochemical probing techniques can provide a wealth of information on nucleotides and sequence stretches of an unliganded riboswitch that interact with each other, they yield limited information about the overall architecture and, in particular, the interhelical organization.…”
Section: What Experimental Methods Grant Insights Into the Free Ribosmentioning
confidence: 99%